Derivation of Quantum Guarded Command Language Program for Average - Telap, Cherry; Pinontoan, Benny; Titaley, Jullia (d'CARTESIAN:Jurnal Matematika dan Aplikasi, 2015)
Has conducted research to determine the derivation of quantum guarded command language (qGCL) program for average. Initially calculation of average value was made in guaded command language (GCL) which is then implemented on a digital computer into the Pascal programming language. Furthermore GCL to calculate the average value was analyzed again to be made in the quantum guarded command language (qGCL). qGCL implementation is on a quantum computer is a future computer could perform calculations very quickly because it uses a superposition state is referred to as quantum bits (qubits). Keywords : GCL, qGCL, Quantum Computer